The recognition and enforcement of foreign divorce judgment rendered in absentia of the defendant: notes to the judicial decree of the Provincial Court of Tarragona, of January 21, 2019 - Heredia Sánchez, Lerdys S. (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
This paper analyzes the Act of the Spanish Court of Appel of Tarragona about the recognition and enforcement of the Judgment of Court of Morocco about a marriage dissolution. The comment refers to the obligation, imposed by the Spanish international private law, to apply the international treaties to which Spain is a party in order to enforcement foreign judicial decisions about divorce, specially, when de defendant is in absentia in the procedure.
Keywords: exequatur procedure; appeal; marriage dissolution; divorce; international treaties